ANALYSIS OF SCIENCE LEARNING MEDIA ON PLANT REPRODUCTION FOR ELEMENTARY SCHOOL STUDENTS - Vera Apriyani; Rahmawati Rahmawati; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
This study aims to analyze the effectiveness of simple experiment-based learning media in the Natural and Social Sciences (IPAS) subject on plant reproduction, specifically on mung beans (Vigna radiata), for elementary school students. The method used was an observational experiment using three aqua bottles filled with soil, each placed in different lighting conditions: full, partial, and no sunlight. Observations over eight days revealed significant differences in growth. The seedlings exposed to full sunlight exhibited optimal growth with the highest number of true leaves and a vibrant green color. Meanwhile, the seedlings exposed to partial sunlight exhibited slowed growth, and those exposed to no light at all exhibited etiolation and ultimately died. These findings confirm that light intensity significantly influences photosynthesis and plant growth, and demonstrate that this simple experimental medium can be an effective, contextual, and enjoyable learning tool for elementary school students in understanding the concept of plant reproduction. With a hands-on approach, students can develop concrete scientific understanding, improve observation skills, and foster critical scientific attitudes and environmental stewardship.